Parcelamento e doses de nitrogênio em cobertura na produção, acúmulo de nutrientes e qualidade de cenoura - Colombari, Lidiane Fernandes [UNESP] (2015)
The objective of this study was to assess the effect of forms of installments and nitrogen rates in covering the production, accumulation of nutrients and quality of carrot. The experiment was conducted in São Manuel Experimental Farm (FCA/UNESP), located in São Manuel-SP, in the period from July to November 2013. The experimental design was a randomized blocks, with nine treatments resulting from factorial 4x2 + control without nitrogen fertilization, with four replications. The first factor consisted of four nitrogen rates in covering (60, 90, 120 and 150 kg ha-1) and the second, parceling in two ways. In the first parceling rates were divided into three applications of 1/3 of the rate and the second parceling was 1/6+2/6+3/6 the dose. Belgrade hybrid was used. Vegetative characteristics (fresh and dry weight of shoot and shoot height), production (roots fresh and dry weight, diameter and length of the roots and yield), content and accumulation of macronutrients (shoot and root) and root physico-chemical characteristics (soluble solids, titratable acidity, soluble solids / titratable acidity, pH, carotenoids content and reducing sugars) were evaluated at the end of the cycle. For most of vegetative characteristics and root production in was obtained quadratic effect for nitrogen levels in coverage, with estimated maximum yield at the rate of 138 kg of N ha-1. The parceling don't influence the levels of macronutrients on leaf analysis, however influenced most vegetative characteristics and root production, with higher values for the parceling 1/6+2/6+3/6. The accumulation of macronutrients by the carrot plant, showed a quadratic effect in function of nitrogen rates in coverage, with the highest accumulation in the parceling 1/3+1/3+1/3 obtained with rates in the between 105 and 127 kg of N ha-1 and parceling 1/6+2/6+3/6 at doses in the between 135 and 140 kg of N ha-1. The decreasing order of ...